Drivers of Russian Industrial Growth in the Face of New Reality - L. V. Obolenskaya; N. M. Abdikeev; O. M. Abrosimova (Мир новой экономики, 2024)
The opportunities for Russia’s economic growth substantiate the relevance of the research in the current conditions. The authors analyze the scientific literature and summarize the approaches to the “locomotives” or “drivers” of growth. In line with the reviewed studies, the authors use the sectoral approach. This considers the important investments presented in different approaches. The purpose of the paper is to identify the sectors of the Russian manufacturing industry that could, with certain government support, act as locomotives of economic growth in the medium and long term. The authors considered the locomotive industries in relation to two interrelated tasks of the investment model of growth. The study uses methods and tools of economic, logical, cause-and-effect analysis, content analysis, as well as forecasting and statistical assessments. The work has identified two groups of engine industries, using forecast-statistical estimates reflecting the impact of external sanctions on the Russian economy. The practical significance of the study is to define the growth driver industries for the further design of measures for the strategic development of these industries.